Expertise and Experience in VR-supported learning: Achieving a deep non-verbal comprehension of four-dimensional space. Issue 152 (August 2021) - Collins, Jonny; Regenbrecht, Holger; Langlotz, Tobias
Highlights: We replicate and validate a historic proposal to investigate constructivist learning Interactive experience in VR has a significant impact on users' conceptual learning There is a unique relationship between expertise and interaction in VR environments Both interaction and theoretical knowledge gain are necessary for effective learning Abstract: Immersive Virtual Reality (VR) has shown to be effective in general training and learning applications, but whether it has potential in understanding and learning complex topics is not well researched. In addition, the role of users' expertise in VR-based learning is not really understood. Here we present findings from our purpose-designed immersive VR system and investigation on whether experts with theoretical knowledge in a certain domain can develop deep non-verbal comprehension beyond pure understanding. Mathematically educated experts as well as non-experts are asked to interact with four-dimensional cubes projected into three-dimensional VR space (hypercubes)—an intentional task not found in real life. In the first of two studies, we validate the feasibility of the principle subject matter, apparatus, and proposed measurements with 22 participants. This study is based on a seminal study proposal from the 1970's. We use the results of this first study to inform a second study based on a philosophical thought experiment known as Mary's Room. With 70 participants we investigate experience, interaction, and prior knowledge, in an immersive VR learning environment. We can show that both experts and non-experts benefit from the immersive interaction with hypercubes. Both groups develop a non-verbal comprehension of this theoretical construct. Surprisingly though, experts, with prior theoretical knowledge, benefit stronger. Our findings have implications for immersive VR learning environments and open a future research space on the importance of and relationships between immersive VR, interaction, understanding, comprehension, and constructivist learning.